Multifunctional fire-retardant coating and preparation method thereof

CN122213810BActive Publication Date: 2026-10-27SHENZHEN LIJIAN BONA TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610457421.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-08
Publication Date
2026-10-27
Estimated Expiration
2046-04-08

AI Technical Summary

Technical Problem

[0005]为了解决膨胀石墨在高温下容易膨胀,进而导致在起火条件达到之前就发生开裂,导致其失去涂层的保护效果和防火效果,本申请提出了一种多功能防火涂料及其制备方法

Benefits of technology

[0028]综上所述,本申请中提供了一种多功能防火涂料,其通过对石墨进行溶胀后,采用原位插层反应接枝聚脲化合物,进而通过聚脲化合物控制膨胀石墨的热分解过程,使其在200℃左右具有较为稳定的耐高温性能,而在超过300℃后可以实现快速膨胀,进而提供良好的耐热和阻燃兼顾的性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1774851224347-000001
    Figure REF-OBJ-1774851224347-000001
Patent Text Reader

Abstract

The application relates to the field of fireproof coatings, in particular to a multifunctional fireproof coating and a preparation method thereof. After graphite is swelled, a polyurea compound is grafted through in-situ intercalation reaction, the thermal decomposition process of the swelled graphite is controlled through the polyurea compound, the swelled graphite has relatively stable high-temperature resistance at about 200 DEG C, can realize rapid expansion when the temperature exceeds 300 DEG C, and thus good heat resistance and fire resistance are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of fire-retardant coatings, and in particular to a multifunctional fire-retardant coating and its preparation method. Background Technology

[0002] Expanded graphite is a commonly used filler in fire-retardant coatings. Due to its unique layered structure and the characteristic of rapid expansion at high temperatures, when exposed to high temperatures or flames, its internal intercalation structure can quickly vaporize and expand the graphite sheets to form an expanded carbon layer with heat insulation and oxygen barrier functions, thereby protecting the substrate and achieving a flame-retardant effect.

[0003] The expansion temperature of expanded graphite is usually in the range of 90 to 300℃, and its initial expansion temperature is usually 140 to 300℃, which can be controlled by adjusting the intercalation structure. For example, graphene that begins to expand at 300℃ can be obtained by oxidation with potassium permanganate and concentrated sulfuric acid (Journal of Hebei University (Natural Science Edition), 2011, Vol. 31 ›› Issue (5):497-501).

[0004] Although the initial temperature of expanded graphite is relatively easy to control, it will still slowly expand under long-term high-temperature conditions. In some long-term high-temperature conditions with fire-resistant requirements, the varnish coating with expanded graphite is very prone to cracking on the surface due to the expansion of expanded graphite in the range of 100-200℃. This not only causes coating loss but also weakens its fire-resistant effect and creates certain safety hazards. Summary of the Invention

[0005] To address the issue that expanded graphite is prone to expansion at high temperatures, leading to cracking before ignition conditions are met and thus losing its protective and fire-retardant effects, this application proposes a multifunctional fire-retardant coating and its preparation method.

[0006] First, this application provides a multifunctional fire-retardant coating, comprising component A and component B, wherein component A comprises the following components in parts by weight: 100 parts epoxy resin 20-30 parts of silicone resin 10-20 parts of composite flame retardant Colorant 0-10 parts Other adjuvants: 0-30 parts The other additives include any number of dispersants, defoamers, leveling agents, antisettling agents, antifungal agents, coupling agents, and thixotropic agents; Component B contains at least a curing agent and an accelerator, and the mass ratio of component A to component B is 1:0.1 to 0.4; Component A and component B also include diluents; The method for preparing the composite flame retardant includes at least the following: S1. Oxidation of graphite using potassium permanganate and concentrated sulfuric acid; S2. After the oxidized graphite is fully soaked and swollen in a non-aqueous solvent, isocyanate is added to load the isocyanate into the graphite interlayer. S3. After dissolving the terminal amino polyether, add the graphite with intercalated isocyanate obtained in step S2 to the solution, and then carry out an in-situ polymerization reaction. S4. In the system of step S3, melamine flame retardant is further added, and after being fully mixed, the solvent is removed to obtain a composite flame retardant.

[0007] In the above scheme, an intercalation in-situ polymerization method is generally adopted. First, active groups are introduced into the graphite through oxidation treatment. Then, isocyanate is preloaded into the graphite interlayer and then undergoes an in-situ polymerization reaction with terminal amino polyether to generate polyurea macromolecular chains that intercalate between the graphite sheets. Under this scheme, on the one hand, polyurea and graphite can form a more robust bonding structure at the nanoscale. The expansion and contraction elasticity of polyurea is used to limit the expansion of graphite in an environment of 100-200℃, forming a more stable structure. At the same time, during the intercalation process, melamine is loaded to construct a complete thermal expansion flame retardant system.

[0008] Based on the above, the polyurea system can rapidly vaporize at around 300℃, while the melamine system also sublimates rapidly. Overall, because polyurea can form a pre-expanded structure at around 300℃, it can have a faster response rate when rapidly expanding at around 300℃. At the same time, the embedded structure can also make the graphite layer itself form a melamine-loaded effect. Melamine flame retardants can not only cause gas diffusion in the system, but also form a condensed flame retardant system. After the expanded graphite expands rapidly, it can help the expanded graphite form a strong flame retardant char layer, and at the same time help the molten polymer form non-combustible drips. The flow of the above drips can be controlled by the expanded graphite, and the overall coating can remain intact during the heating process, providing good heat resistance and flame retardant effect.

[0009] Preferably, the epoxy resin is a phenolic epoxy resin, and / or the silicone resin is a methylphenyl silicone resin or a phenyl silicone resin, and / or the curing agent is a polyamide.

[0010] In the above scheme, phenolic epoxy resin itself has higher crosslinking density and heat resistance, and it has longer stability and heat decomposition resistance at 200℃. At the same time, the introduction of phenyl groups into the side chains of silicone resin can also improve the heat resistance of the system.

[0011] Meanwhile, in the above system, the use of polyamide as a curing agent can further improve the network crosslinking performance and adhesion of epoxy resin, and has good processing performance, which can improve the fluidity of the system.

[0012] Preferably, the graphite is any one of natural flake graphite, expandable graphite, and artificial graphite, and / or the isocyanate is selected from any one or more combinations of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), HDI trimer, and isophorone diisocyanate (IPDI), and / or the terminal amino polyether is polyetheramine D230.

[0013] In the above system, D230 has a moderate molecular weight, which can better control the interlayer structure of graphite. It ensures good flexibility of the system and avoids intercalation difficulties due to excessively long chain segments. Moreover, it can be released quickly at 300℃, which improves the leveling performance and adhesion of the coating as a whole, while also providing better heat resistance. The response rate is faster than other amino-terminated polyether systems.

[0014] Preferably, the mass of the isocyanate is 0.1 to 0.3 times the mass of the oxidized graphite, and / or the molar ratio of the terminal amino polyether to the isocyanate is 1.1 to 1.2:1.

[0015] Overall, within the aforementioned isocyanate mass range, a good intercalation saturation rate can be provided. A relatively low amount of isocyanate is used, mainly to maintain the strength and film-forming properties of the coating itself, improve the adhesion of the coating, and at the same time, avoid the generation of bubbles in the air by residual isocyanate. Using an appropriate amount of high-grade terminal amino polyether can also improve the dispersion performance of the system, while helping to improve the reaction rate of the system. It also avoids the char layer embrittlement and increased thermal conductivity caused by excessive polyurea, thereby improving the overall integrity in the flame retardant process, and taking into account both response rate and thermal insulation performance.

[0016] Preferably, the melamine flame retardant is melamine polyphosphate or melamine urate, and / or the mass of the melamine flame retardant is 0.1 to 0.2 times the mass of the oxidized graphite.

[0017] In the aforementioned system, melamine polyphosphate or melamine urate can better match the overall response temperature, which is slightly higher than 300℃. This allows for rapid synergistic gas production during polyurea decomposition, quickly releasing phosphoric acid at high temperatures to form a carbonized layer. Simultaneously, it avoids the excessively porous and weakened carbon layer caused by excessive gas supply. In contrast, ordinary melamine decomposes at 300℃, making it more difficult to achieve synchronous synergy with the polyurea system and more prone to surface cracking under high-temperature conditions.

[0018] Preferably, in step S1, the mass of potassium permanganate is 0.01 to 0.05 times the mass of graphite, and / or the mass of concentrated sulfuric acid is 1 to 3 times the mass of graphite, and / or the reaction temperature is 20 to 40°C, and / or the oxidation time is 0.5 to 2 hours.

[0019] In the above scheme, the mass of potassium permanganate is 0.01 to 0.05 times the mass of graphite. This mild oxidation condition introduces an appropriate amount of oxygen-containing functional groups (such as hydroxyl and carboxyl groups) between the graphite layers while maintaining the basic integrity of the graphite crystal structure. Below 0.01 times the mass, the oxidation degree is insufficient, making subsequent intercalation difficult; above 0.05 times the mass, excessive oxidation leads to graphite layer damage and decreased expansion performance. The amount of concentrated sulfuric acid directly affects the intercalation performance of the system. Within this reaction range, it provides good reaction space for the subsequent entry of isocyanate and grafting of the polyurea system, while also ensuring the overall strength and leveling properties of the system. Overall, the above reaction system conditions are mild and conducive to large-scale industrial production.

[0020] Preferably, in step S4, any number of pentaerythritol and dipentaerythritol are added, with a mass of 0.1 to 0.2 times that of graphite oxide.

[0021] In the above scheme, pentaerythritol / dipentaerythritol is introduced as an auxiliary carbon source: pentaerythritol and its dimer are rich in hydroxyl groups, which can undergo esterification reaction with acid sources such as ammonium polyphosphate and melamine at high temperature to form carbon intermediates, which significantly enhances the carbon skeleton density of the expanded carbon layer.

[0022] Preferably, in step S2, the solvent is any number of toluene, xylene, DMF, NMP, acetone, and isobutyl ketone, and / or the swelling temperature is 40–80°C, and / or the swelling time is 2–6 h, and / or the reaction time after swelling is 2–6 h.

[0023] Overall, the solvents described above can adequately swell graphite and better dissolve components such as isocyanates, thus improving the swelling system, ensuring the reaction occurs fully within the graphite, and enhancing the intercalation effect. Simultaneously, this system also facilitates solvent recovery, contributing to cost savings and pollution reduction in industrial production processes.

[0024] Preferably, in step S3, the in-situ polymerization temperature is 40–80°C, and / or the in-situ polymerization reaction time is 12–24 h.

[0025] Overall, since the reaction occurs more within the intercalation layer, in-situ polymerization requires a relatively longer time. Under the above-mentioned temperature and reaction time, polyurea can form a more uniform crosslinking system, the crosslinking region is controllable, and the intercalation effect is better.

[0026] This application also includes a method for preparing the above-mentioned multifunctional fire-retardant coating, comprising the following steps: Epoxy resin, silicone resin, composite flame retardant, colorant, diluent and other additives are mixed, ground and dispersed, and the viscosity is adjusted to obtain component A. Curing agent, accelerator and remaining diluent are mixed and stirred evenly to obtain component B. Component A and component B are mixed evenly in proportion to obtain fire-retardant coating.

[0027] In the above scheme, the process is relatively simple and the batch process is stable. By grinding and dispersing and adjusting the viscosity, the flame retardant filler and other components can form a more uniform dispersion system, which can avoid stratification and improve the overall leveling performance, film forming performance and adhesion performance.

[0028] In summary, this application provides a multifunctional fire-retardant coating that, after swelling graphite, uses in-situ intercalation reaction to graft polyurea compounds, thereby controlling the thermal decomposition process of the expanded graphite through the polyurea compounds. This results in relatively stable high-temperature resistance at around 200°C, while rapid expansion occurs above 300°C, thus providing excellent heat resistance and flame retardancy. Detailed Implementation

[0029] The technical solution of this application will be further described through the following specific embodiments.

[0030] First, by modifying graphite through the following preparation examples, a series of expanded graphite systems with intercalated grafted polyurea can be obtained.

[0031] Preparation Example 1 provides a method for preparing a composite flame retardant, specifically including the following preparation steps: S1. Add natural flake graphite (150 mesh) to a reaction vessel, add 3% potassium permanganate by weight of graphite, and then slowly add concentrated sulfuric acid at twice the weight of graphite. Control the reaction temperature at 30±2℃. After the reaction is complete, pour in a large amount of ice water to dilute, let it stand and settle, then filter and wash repeatedly with deionized water until neutral, and then vacuum dry at 60℃ for 5 hours.

[0032] S2. Disperse the oxidized graphite from step S1 in DMF at a mass ratio of 1:10, heat to 60°C, stir for 4 hours to allow it to swell, then add MDI at a mass ratio of 0.25 times that of graphite to the system, maintain the temperature at 60°C, continue stirring for 4 hours, then quickly filter and wash three times with toluene, and vacuum dry at 60°C for 12 hours.

[0033] S3. Polyetheramine D230 is pre-dissolved in DMF at a mass ratio of 1:10. Then, the isocyanate-loaded graphite obtained in step S2 is slowly and evenly added in batches over 5 minutes to the DMF solution of amino-terminated polyether. The mixture is heated to 60°C and reacted for 18 hours. After cooling to 20°C, a mixed reaction solution is obtained. The molar ratio of polyetheramine D230 to MDI is 1.2:1, that is, its mass is 1.10 times the mass of MDI.

[0034] S4. Add melamine polyphosphate (0.1 times the mass of graphite) and pentaerythritol (0.1 times the mass of graphite) to the mixed reaction solution, start high-speed stirring, stir at 200 rpm at 30±2℃ for 30 min, then centrifuge, and vacuum dry at 50℃ for 4 hours to obtain the composite flame retardant.

[0035] Preparation Example 2 differs from Preparation Example 1 in that polyetheramine D230 is replaced with polyetheramine D400 in an equimolar amount. Specifically, the mass of polyetheramine D400 is 1.92 times the mass of MDI.

[0036] Preparation Example 3 differs from Preparation Example 1 in that polyetheramine D230 is replaced with polyetheramine D2000 in an equimolar amount. Specifically, the mass of polyetheramine D400 is 9.6 times the mass of MDI.

[0037] Preparation Example 4 differs from Preparation Example 1 in that the molar ratio of polyetheramine D230 to MDI is 1:1.0.

[0038] Preparation Example 5 differs from Preparation Example 1 in that polyetheramine D230 is replaced with EDA (ethylenediamine) in an equimolar amount. Specifically, the mass of EDA is 0.29 times the mass of MDI.

[0039] Preparation Example 6 differs from Preparation Example 1 in that polyetheramine D230 is replaced by an equimolar amount of HMDA (1,6-hexanediamine). Specifically, the mass of MXDA is 0.56 times the mass of MDI.

[0040] Preparation Example 7 differs from Preparation Example 1 in that step S3 is omitted.

[0041] Preparation Example 8 differs from Preparation Example 1 in that pentaerythritol is not added in step S4.

[0042] Preparation Example 9 differs from Preparation Example 1 in that, in step S4, the mass of pentaerythritol is 0.2 times the mass of graphite.

[0043] Preparation Example 10 differs from Preparation Example 1 in that, in step S4, the mass of pentaerythritol is 0.3 times the mass of graphite.

[0044] Preparation Example 11 differs from Preparation Example 1 in that, in step S4, pentaerythritol is replaced by bispentaerythritol by an equal mass.

[0045] Preparation Example 12 differs from Preparation Example 1 in that melamine polyphosphate is not added in step S4.

[0046] Preparation Example 13 differs from Preparation Example 1 in that, in step S4, the mass of melamine phosphate is 0.2 times the mass of graphite.

[0047] Preparation Example 14 differs from Preparation Example 1 in that, in step S4, melamine phosphate is replaced by melamine urate by an equal mass.

[0048] Preparation Example 15 differs from Preparation Example 1 in that melamine phosphate is replaced by melamine by an equal mass.

[0049] Preparation Example 16 differs from Preparation Example 1 in that melamine phosphate is replaced by melamine polyphosphate by an equal mass.

[0050] Preparation Example 17 differs from Preparation Example 1 in that, in step S2, no pre-swelling is performed, and MDI is directly added for loading treatment.

[0051] Based on the above preparation examples, using them as composite flame retardants to prepare multifunctional fire-retardant coatings yields Examples 1 to 17. Examples 1 to 17 respectively used the composite flame retardants from Preparation Examples 1 to 17, and the amount of composite flame retardant added and other preparation conditions remained unchanged, as detailed below: Component A is prepared according to the following mass ratio: Commercially available F51 phenolic epoxy resin (epoxy value 181g / 100ep) 100 parts Methylphenyl silicone resin (SILRES® 604) 25 parts 15 parts of composite flame retardant Titanium dioxide (colorant, 300 mesh) 5 parts Dispersant (Anti-Terra-U100, polyamide wax) 1 part Defoamer (BYK-141) 1 part Thixotropic agent (fumed silica, 500 mesh) 2 parts Diluent (xylene and n-butanol, mass ratio 8:2) 50 parts Coupling agent (KH-560) 0.5 parts Component B is prepared according to the following mass ratio: Polyamide curing agent (650#) 100 parts Accelerator (DMP-30) 6 parts Diluent (xylene and n-butanol, mass ratio 8:2) 30 parts After mixing the components in component A, disperse them in a high-speed disperser for 30 minutes, then transfer them to a sand mill to grind them to a fineness of ≤50 μm, filter them to obtain component A. Mix the materials in component B and disperse them in a high-speed disperser for 10 minutes. Then mix component A and component B in a mass ratio of 3:1 and mature them for 15 minutes before application.

[0052] For ease of testing, in this application, except for necessary tests which are otherwise specified, all other coated substrates are uniformly made of sandblasted iron plates, with the dry film thickness controlled at 2.0±0.1mm, and cured for 7 days under standard conditions (23±2℃, relative humidity 50±5%), and tested according to the following method.

[0053] 1. Adhesion test: Refer to GB / T 5210 "Paints and Varnishes - Pull-off test" and conduct the experiment using a pull-out tester to determine the vertical pull-out force.

[0054] 2. Paint film flexibility test: Refer to the method in Chapter 4 of GB / T 1731-2020 "Test Method for Flexibility of Paint Film and Putty Film", use a flexibility tester, and record the minimum diameter of the shaft without cracking.

[0055] 3. Long-term stability at 200℃: After the paint film is coated on the substrate and cured, it is placed at 200℃ for 120 hours, and then the adhesion and flexibility are tested.

[0056] 4. Initial expansion temperature: Place the coating on a glass slide of a hot-stage microscope and increase the temperature at a rate of 2.5℃ / min. Record the temperature at which the volume expansion first occurs.

[0057] 5. Fire resistance limit test: The fire resistance limit is determined by heating according to the temperature rise curve of GB / T 9978.1 standard.

[0058] The experimental results for the above embodiments are shown in Table 1.

[0059] In the above experiments, the effects of different modifications to flake graphite on the system's heat resistance and fire resistance were mainly studied. First, comparing Examples 1, 7, and 17, in Example 17, without swelling, grafting mainly occurred on the surface of the flake graphite. MDI was adsorbed onto the surface of the flake graphite through π-π stacking or physical adsorption, resulting in a significant decrease in heat resistance and a certain reduction in the fire resistance limit. In Example 7, without polyurea grafting, not only was the heat resistance weakened, but the initial expansion temperature also increased, and the fire resistance limit also decreased to some extent.

[0060] In Examples 2-6, the selection of polyetheramines was adjusted. EDA was used in Preparation Example 5, and HMDA was used in Preparation Example 6. The performance of these polyetheramines in generating gas upon heating was significantly weakened, resulting in a decrease in both the fire resistance limit and heat resistance, and a slight increase in the initial expansion temperature. In Preparation Examples 2-3, the type of polyetheramine was adjusted. It can be seen that compared to polyetheramine D230, polyetheramines D400 and D2000 were less likely to enhance heat resistance. This may be because only D230 can better balance intercalation performance and heat resistance, and has a better effect on preventing cracking. While polyetheramines D400 and D2000 improved heat resistance to some extent compared to the unmodified solution, they more or less negatively impacted the flame retardant effect of the system, possibly due to their greater tendency to form grafted intercalations on the outer surface.

[0061] In Preparation Examples 8-11, the addition of pentaerythritol was adjusted, and it can be seen that the flame retardant properties of the system were significantly weakened in the scheme without the addition of pentaerythritol. In Examples 12-16, various different tripolyphosphate or tripolyphosphate systems were used. It can be seen that melamine urate and melamine phosphate provided better flame retardant properties compared to melamine polyphosphate and melamine itself, and the response temperature was easier to control and concentrate at around 320°C, resulting in a lower overall response temperature.

[0062] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A multifunctional fire-retardant coating, characterized in that, It includes component A and component B, wherein component A comprises the following components by mass parts: 100 parts epoxy resin 20-30 parts of silicone resin 10-20 parts of composite flame retardant Colorant 0-10 parts Other adjuvants: 0-30 parts The other additives include any number of dispersants, defoamers, leveling agents, antisettling agents, antifungal agents, coupling agents, and thixotropic agents; Component B contains at least a curing agent and an accelerator, and the mass ratio of component A to component B is 1:0.1 to 0.4; Component A and component B also include diluents; The preparation method of the composite flame retardant is at least as follows: S1. Oxidation of graphite using potassium permanganate and concentrated sulfuric acid; S2. After the oxidized graphite is fully impregnated and swollen in a non-aqueous solvent, isocyanate is added to load the isocyanate into the graphite interlayer. The solvent is any number of toluene, xylene, DMF, NMP, acetone, and isobutyl ketone. The swelling temperature is 40-80°C, the swelling time is 2-6 hours, the reaction time after adding isocyanate is 2-6 hours, and the mass of isocyanate is 0.1-0.3 times the mass of the oxidized graphite. S3. After dissolving the terminal amino polyether, add the graphite with intercalated isocyanate obtained in step S2 to the solution, and then carry out an in-situ polymerization reaction. The terminal amino polyether is polyetheramine D230, the molar ratio of the terminal amino polyether to isocyanate is 1.1 to 1.2:1, the temperature of the in-situ polymerization is 40 to 80°C, and the reaction time is 12 to 24 hours. S4. In the system of step S3, melamine flame retardant is further added, and after being fully mixed, the solvent is removed to obtain a composite flame retardant.

2. The multifunctional fire-retardant coating according to claim 1, characterized in that, The epoxy resin is a phenolic epoxy resin, and / or the silicone resin is a methylphenyl silicone resin or a phenyl silicone resin, and / or the curing agent is a polyamide.

3. The multifunctional fire-retardant coating according to claim 1, characterized in that, The graphite is any one of natural flake graphite, expandable graphite, and artificial graphite, and / or the isocyanate is selected from any one or a combination of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, HDI trimer, and isophorone diisocyanate.

4. The multifunctional fire-retardant coating according to claim 1, characterized in that, The melamine flame retardant is melamine polyphosphate or melamine urate, and / or the mass of the melamine flame retardant is 0.1 to 0.2 times the mass of the oxidized graphite.

5. The multifunctional fire-retardant coating according to claim 1, characterized in that, In step S1, the mass of potassium permanganate is 0.01 to 0.05 times the mass of graphite, and / or the mass of concentrated sulfuric acid is 1 to 3 times the mass of graphite, and / or the reaction temperature is 20 to 40°C, and / or the oxidation time is 0.5 to 2 hours.

6. The multifunctional fire-retardant coating according to claim 1, characterized in that, In step S4, any number of pentaerythritol and dipentaerythritol are added, with a mass of 0.1 to 0.2 times that of graphite oxide.

7. The method for preparing the multifunctional fire-retardant coating according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Oxidation of graphite using potassium permanganate and concentrated sulfuric acid; S2. After the oxidized graphite is fully impregnated and swollen in a non-aqueous solvent, isocyanate is added to load the isocyanate into the graphite interlayer. The solvent is any number of toluene, xylene, DMF, NMP, acetone, and isobutyl ketone. The swelling temperature is 40-80°C, the swelling time is 2-6 hours, the reaction time after adding isocyanate is 2-6 hours, and the mass of isocyanate is 0.1-0.3 times the mass of the oxidized graphite. S3. After dissolving the terminal amino polyether, add the graphite with intercalated isocyanate obtained in step S2 to the solution, and then carry out an in-situ polymerization reaction. The terminal amino polyether is polyetheramine D230, the molar ratio of the terminal amino polyether to isocyanate is 1.1 to 1.2:1, the temperature of the in-situ polymerization is 40 to 80°C, and the reaction time is 12 to 24 hours. S4. In the system of step S3, melamine flame retardant is further added, and after being thoroughly mixed, the solvent is removed to obtain a composite flame retardant. S5. Mix epoxy resin, silicone resin, the composite flame retardant, colorant, diluent and other additives, grind and disperse, adjust viscosity to obtain component A, mix curing agent, accelerator and remaining diluent, stir evenly to obtain component B, mix component A and component B evenly at a mass ratio of 1:0.1 to 0.4 to obtain fireproof coating.

Citation Information

Patent Citations

  • In situ polymerization intumescent flame retardant and preparation raw materials as well as preparation method and application thereof

    CN110183728A

  • Solvent-free organosilicone-epoxy fireproof coating for steel structure as well as preparation method and application of solvent-free organosilicone-epoxy fireproof coating

    CN118599400A

  • Polyurethane-graphite oxide composite material, method for its preparation and its use as a flame retardant and as a fire-proof seal

    US20060293443A1